Analisis Dan Perancangan Sistem Informasi Penilaian Kinerja Pegawai (Studi Kasus PT Multi Anugrah Abadi Jambi) - Farras, Faisal; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2021)
PT Multi Anugrah Abadi does not yet have a computerized employee performance appraisal information system technology to measure employee performance and data processing. In the process of performance appraisal is carried out using a performance appraisal form in the form of a paper which must be filled in by each department head for the performance of his subordinates. To know the progress of employee performance appraisals, the HRD Department must recapitulate the results of the assessment for each period using office excel. So the authors aim to analyze and design an employee performance appraisal information system by implementing a web-based performance appraisal information system which is expected to facilitate the employee performance appraisal process. This research framework consists of literature study, data collection, data analysis, system development, and reporting. The author's system development method is to design use cases, activity diagrams, class diagrams and system prototypes that refer to the field of software engineering (RPL). This employee performance appraisal information system can perform the performance appraisal process and manage employee data properly in order to streamline and streamline the performance appraisal process and speed up time and minimize the error rate when entering data. The author also expects this system to be developed again and officers who can be responsible for operating the system to prevent fraud.